LTBP2 is a prognostic marker in head and neck squamous cell carcinoma - Han, Liang (Oncotarget, 2016)
Latent transforming growth factor (TGF)-beta binding protein 2 (LTBP2) belongs to the fibrillin/LTBP extracellular matrix glycoprotein superfamily. It plays vital roles in tumorigenesis through regulating TGFβ activity, elastogenesis and maintenance of the extracellular matrix (ECM) structure. In this study, we determined the expression levels of LTBP2 mRNA and protein in head and neck squamous cell carcinoma (HNSCC) tissues and adjacent normal tissues by quantitative reverse transcription PCR (qRT-PCR) and tissue microarray immunohistochemistry analysis (TMA-IHC) respectively. LTBP2 protein levels in cancer tissues were correlated with HNSCC patients' clinical characteristics and overall survival. Both LTBP2 mRNA and protein levels were significantly higher in HNSCC tissues than in adjacent normal tissues. High LTBP2 protein level was associated with lymph node metastasis and higher pTNM stages. High LTBP2 protein level is an independent prognostic marker in HNSCC. Our data suggest that LTBP2 acts as an oncogene in HNSCC development and progression. Detection of LTBP2 expression could be a useful prognosis marker and targeting LTBP2 may represent a novel strategy for cancer treatment through regulating activities of TGFβ.